Methane escape from lowland terrestrial seepages - links to deglaciation and permafrost dynamics - Ciric, Emma Nika (2020)
In the Norwegian archipelago of Svalbard, 90%-100% of exposed land is underlain by continuous permafrost. Permafrost is estimated to store over 1600 gigatons of carbon worldwide. Pingos, features that only exist in permafrost, ventilate methane in much the same manner as pockmarks can ventilate methane clathrates on the ocean floor. In winter 2019, pingos identified on satellite imagery were studied in the field via water samples. This was done to better understand these uncommon periglacial features and of the methane they release. A database was created using elevation datasets, GIS analysis, winter satellite photography, and geological data to identify pingos in Svalbard as well as the factors that influence their formation and behaviour. The spatial distribution of pingos and fault lines suggests a relationship between fault zones and the formation of pingos, possibly due to the discontinuity caused by the faults allowing for easier flow of groundwater. In addition, carbon dioxide and methane had a correlation which is probably associated to the microbial processes leading to the formation of methane. Deuterium was another important compound, likely due to the marine sediments within the Holocene marine limit. A predictive model was then established to show the relationship of carbon dioxide and deuterium with methane. This model estimates the amount of methane ventilated based on other compounds measured in pingos. By combining these scientific approaches, this data provides a step forward in understanding methane reservoirs within permafrost environments, particularly relevant in an unstable and changing climate.